Helminth fauna in sable (Mertes zibellina Linnaeus, 1758) of Yakutia - L. M. Kokolova; A. I. Illarionov (Российский паразитологический журнал, 2019)
Objective of research: The study of helminth fauna in sables of Yakutia. Materials and methods: Sables caught in 2016-2017 were investigated for helminthic infection. We used the methods of complete and incomplete helminthological dissection, and the method of trichinelloscopy of muscle tissue. The sable’s intestine was dissected and examined along the whole length by the method of sequential washing, the contents of the intestine - by Fulleborn and Bermann methods. 462 sables were examined. Taxonomic examinations were conducted according to the Key to invertebrates of Kozlov M.A. and the Atlas of the most common helminths of the agricultural animals of Kapustin V.F. Results and discussion: It was found that sables inhabiting the territory of Yakutia are infected with 27 helminth species belonging to three classes: Cestoda, Nematoda, and Acanthocephala. 6 species of cestodes were detected: Mesocestoides lineatus in 12 sables (Intensity of Infection 1-3 ind.); Taenia hydatigenа in 15 sables (3,24 %), II 1-7; T. Sibirica in 23 (4,98 %), II 1-6; T skrjabini in 14 (3,03 %), II 3-5; T martis in 41 (8,87 %), II 2-7; T mustelae in 25 (5,41 %), II 1-3 ind. The average intestinal infection rate with Taenia spp. did not exceed 7 ind. Three acanthocephalan species were found in the intestine of sables: Macrocanthorynchus catulinus, Moniliformis clarki, Corynosoma strumosum sp. Intensity of infection was on average 2-5 ind. 18 trematode species were detected in sables: Ascaris columnaris, Mastophorus muris, Molineus patens, Filaroides martis, Sobolevingylus petrovi, Soboliphyme baturini, Capillaria putorii, Skrjabingulus nasola, Physaloptera sibirica, Uncinaria stenocephala, Mustelivingylus skrjabini, Thominx asadovi, Trichocephalus vulpis, Crenosoma petrowi, Syphacia obvelata, Physaloptera sibirica, Trichinella spiralis (in muscle tissue). So, 240 (51,94 %), of 462 examined sable carcasses were infected; 96 sables were infected with two, and 38 sables with three helminth species. Seven species discovered in Yakutia for the first time were added to the helminth fauna of sable. Sables of both sexes were equally infected.